Generation of realistic images from human drawn sketches using deep learning - Mahbub, Mohammed Julfikar Ali; Rahmatullah, S. Afsan; Rahman, G M Sohanur; Zillanee, Abu Hasnayen; Akib, Aknur Kamal (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.